HO‐1 downregulation favors BRAFV600 melanoma cell death induced by Vemurafenib/PLX4032 and increases NK recognition. Issue 7 (24th August 2019) - Furfaro, Anna L.; Ottonello, Selene; Loi, Giulia; Cossu, Irene; Piras, Sabrina; Spagnolo, Francesco; Queirolo, Paola; Marinari, Umberto M.; Moretta, Lorenzo; Pronzato, Maria A.; Mingari, Maria C.; Pietra, Gabriella; et al.
Abstract : Heme oxygenase 1 (HO‐1) plays a pivotal role in preventing cell damage. Indeed, through the antioxidant, antiapoptotic and anti‐inflammatory properties of its metabolic products, it favors cell adaptation against different stressors. However, HO‐1 induction has also been related to the gain of resistance to therapy in different types of cancers and its involvement in cancer immune‐escape has been hypothesized. We have investigated the role of HO‐1 expression in Vemurafenib‐treated BRAF V600 melanoma cells in modulating their susceptibility to NK cell‐mediated recognition. Different cell lines, isolated in house from melanoma patients, have been exposed to 1–10 μM PLX4032, which efficiently reduced ERK phosphorylation. In three lines, Vemurafenib was able to induce only a limited decrease in cell viability, while HO‐1 expression was upregulated. HO‐1 silencing/inhibition was able to induce a further significant reduction of Vemurafenib‐treated melanoma viability. Moreover, while NK cell degranulation and killing activity were decreased upon interaction with melanoma exposed to Vemurafenib, HO‐1 silencing was able to completely restore NK cell ability to degranulate and kill. Furthermore, melanoma cell treatment with Vemurafenib downregulated the expression of ligands of NKp30 and NKG2D activating receptors, and HO‐1 silencing/inhibition was able to restore their expression. Our results indicate that HO‐1 downregulation can both improve the efficacy of Vemurafenib on melanoma cells and favor melanoma susceptibility to NK cell‐mediated recognition and killing. Abstract : What's new? Even though significant improvements have been achieved in the therapy of mutated BRAF V600 melanomas with the use of specific inhibitors, tumor relapse occurs frequently. This study shows that exposure to Vemurafenib induces HO‐1 upregulation in primary BRAF V600 melanoma cell lines, limiting the efficacy of the drug. Induction of HO‐1 impairs melanoma cell expression of specific ligands recognized by NK cells, reducing tumor immunogenicity. Importantly, HO‐1 silencing and pharmacological inhibition restore expression of NK cell activator ligands. The findings highlight HO‐1 as a new potential candidate to improve the efficacy of targeted therapies and NK cell‐mediated killing of BRAF inhibitor‐treated cells.